Electrostatic Dust-Acoustic Rogue Waves in an Electron Depleted Dusty Plasma - Jebun Naher Sikta; Nure Alam Chowdhury; Abdul Mannan; Sharmin Sultana; A. A. Mamun (Plasma, 2021)
The formation of gigantic dust-acoustic (DA) rouge waves (DARWs) in an electron depleted unmagnetized opposite polarity dusty plasma system is theoretically predicted. The nonlinear Schrödinger equation (NLSE) is derived by employing the reductive perturbation method. It is found that the NLSE leads to the modulational instability (MI) of DA waves (DAWs), and to the formation of DARWs, which are caused by to the effects of nonlinearity and dispersion in the propagation of DAWs. The conditions for the MI of DAWs and the basic properties of the generated DARWs are numerically identified. It is also seen that the striking features (viz., instability criteria, amplitude and width of DARWs, etc.) of the DAWs are significantly modified by the effects of super-thermality of ions, number density, mass and charge state of the plasma species, etc. The results obtained from the present investigation will be useful in understanding the MI criteria of DAWs and associated DARWs in electron depleted unmagnetized opposite polarity dusty plasma systems like Earth’s mesosphere (where the D-region plasma could suffer from electron density depletion), cometary tails, Jupiter’s magnetosphere, and F-ring of Saturn, etc.